EFFECTS OF AUTOLOGOUS PLASMINOGEN ON ANGIOSTATIN LEVELS AND MATRIX METALLOPROTEINASE ACTIVITY IN THE HEALING OF A CHRONIC VENOUS SKIN ULCER - Petrenko О.M.; Badziukh, S.V.; Tykhomyrov А.О. (World of Medicine and Biology, 2025)
This clinical case report describes the application of autologous plasminogen to a chronic venous skin ulcer of six years’ duration and its effects on wound healing, proteinase activity, and angiogenesis regulation in the affected tissue. Plasminogen was isolated from the patient’s blood plasma and applied locally every two days for twenty days. Wound size was tracked through planimetric analysis, while levels of protein markers in skin biopsies were assessed using immunoblot analysis and zymography assay. By the twenty-fourth day, the ulcer area has reduced significantly, and this improvement was accompanied by a marked decline in both angiogenesis inhibitors and enzymes associated with tissue degradation. These findings suggest that the normalization of molecular processes induced by plasminogen plays a crucial role in restoring reparative functions in chronic wounds. This is the first report documenting the clinical benefits of autologous plasminogen in treating non-healing lower limb ulcers associated with venous insufficiency.